The sociopragmatics of attitude datives in Levantine Arabic - Haddad, Youssef A., 1972- (Edinburgh University Press, 2018)
This book analyses data from a variety of sources, including soap operas, movies, plays, talk shows and other audiovisual material, to examine attitude datives in Levantine Arabic. It examines four types of interpersonal pragmatic marker: topic/affectee-oriented, speaker-oriented, hearer-oriented and subject-oriented.